2020
DOI: 10.1590/0074-02760190298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of El Niño-Southern Oscillation on human visceral leishmaniasis in the Brazilian State of Mato Grosso do Sul

Abstract: BACKGROUND Leishmaniases are considered a major public health problem in South America, specifically in Brazil. Moreover, the transmission and epidemiology of leishmaniasis are possibly associated with climatic and environmental variations. OBJECTIVE This study aimed to assess the association between the extreme climatic phenomenon El Niño-Southern Oscillation (ENSO), the maximum and minimum variations of temperature, precipitation, and soil moisture and the incidence of visceral leishmaniasis (VL) in Mato Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
(35 reference statements)
0
11
0
1
Order By: Relevance
“…ENSO indices were correlated with the incidences of diverse infectious disease in the past illustrating how ENSO influence transmission mechanisms of various infectious tropical diseases by modulating the local weather. That includes arthropod-borne parasitic infections malaria and leishmaniasis [33,34], mosquito-borne viral infections like dengue [17], robovirus diseases like hantavirus infections [35]; hand, foot, and mouth disease, a viral disease transmitted by feco-oral route as well as respiratory route [36]; and feco-orally transmitted bacterial infection cholera [18]. IOD was described to modulate the incidence of dengue [17]; chikungunya, an arboviral disease [37]; and cholera [18].…”
Section: Comparison Of Our Results With That Of Similar Past Studies and Discussionmentioning
confidence: 99%
“…ENSO indices were correlated with the incidences of diverse infectious disease in the past illustrating how ENSO influence transmission mechanisms of various infectious tropical diseases by modulating the local weather. That includes arthropod-borne parasitic infections malaria and leishmaniasis [33,34], mosquito-borne viral infections like dengue [17], robovirus diseases like hantavirus infections [35]; hand, foot, and mouth disease, a viral disease transmitted by feco-oral route as well as respiratory route [36]; and feco-orally transmitted bacterial infection cholera [18]. IOD was described to modulate the incidence of dengue [17]; chikungunya, an arboviral disease [37]; and cholera [18].…”
Section: Comparison Of Our Results With That Of Similar Past Studies and Discussionmentioning
confidence: 99%
“…We inferred that the marked decrease in the number of cases could be related to the El Niño-Southern Oscillation phenomenon and hurricane activity in the Atlantic Ocean during 2012. 67 These meteorological events trigger changes in rainfall, humidity, and continental temperature patterns, 68 and, when rainfall increases above average, there is less organic matter available for the development of sandflies, [69][70][71] leading to a reduction in leishmaniasis transmission rates. 72 This negative impact on the occurrence of VL has been documented in the Andean region 73 and Venezuela.…”
Section: Discussionmentioning
confidence: 99%
“…72 This negative impact on the occurrence of VL has been documented in the Andean region 73 and Venezuela. 74 However, da Silva Neto et al 68 showed that, in 2012, VL had an increase in incidence (12.37 cases/100,000 inhabitants) in the state of Mato Grosso do Sulen, an area in southern Brazil with particular geographic Incidence is per 100,000 inhabitants. The map was constructed using QGIS software.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha demostrado que los vectores de leishmaniasis son sensibles al cambio climático, se ven fuertemente afectados por lluvias, precipitaciones, temperatura ambiental, humedad atmosférica, a fenómenos El Niño y La Niña, etc. Comprender el rol de los factores ambientales y bioclimáticos en la distribución del vector y la ocurrencia de casos de leishmaniasis proveerá una guía para los responsables en salud pública en la creación e implementación de políticas más efectivas para su control y prevención 20,[105][106] .…”
Section: Controlunclassified